Do undergraduate majors or Ph.D. students affect faculty size? - William E. Becker; William H. Greene; John J. Siegfried (Center for Economic Studies and ifo Institute (CESifo), 2010)
Regression analysis using panel data for 42 colleges and universities over 14 years suggests that the economics faculty size of universities offering a Ph.D. in economics is determined primarily by the long-run average number of Ph.D. degrees awarded annually; the number of full-time faculty increases at almost a one-for-one pace as the average number of Ph.D.s grows. Faculty size at Ph.D. granting universities is largely unresponsive to changes in the contemporaneous number of undergraduate economics degrees awarded at those institutions. Similarly, faculty size at colleges where a bachelor's is the highest degree awarded is responsive to the long and short term average number of economics degrees awarded but not the annual changes in BS and BA degrees awarded in economics.
Keywords: A22; A23; C23; J21; 330; faculty size; student body; Ph.D. degrees; bachelor degrees; Wirtschaftshochschule; Betriebsgröße; Studierende; Bildungsabschluss; Schätzung; USA